Hubungan Kemampuan Literasi dan Numerasi Murid dengan Iklim Keamanan Sekolah di Sulawesi Tengah - Ratna Dwi Rahayu; Wilda Wilda; Haeruddin Haeruddin (Universitas Muhammadiyah Surabaya, 2026)
Literacy, numeracy, and school safety are key aspects that shape students' learning experiences. Although these components are important, their relationships are rarely studied simultaneously. This study analyzes the relationship between literacy and numeracy skills and school safety climate in junior high schools (SMP) and Islamic junior high schools (MTS) using a quantitative correlational design with data from the 2024–2025 Education Report. A total of 52 schools were included through total sampling, and data were analyzed using descriptive statistics, Spearman correlation, and binary logistic regression. Results indicate that literacy, numeracy, and school safety vary across schools. Literacy was not significantly associated with school safety (ρ = 0.173; p = 0.221). Numeracy skills showed a significant positive relationship (ρ = 0.418; p = 0.002) and increased the likelihood of a school having a good safety climate (p = 0.005; Exp(B) = 8.393), although the contribution was small (1.7%). These findings suggest that numeracy skills can support a safer school environment.